Everyday memory measures in multiple sclerosis: a systematic review - das Nair, Roshan; Griffiths, Holly; Clarke, Sara; Methley, Abigail; Kneebone, Ian; Topcu, Gogem (Taylor & Francis, 2019)
Everyday memory is one of the most affected cognitive functions in Multiple Sclerosis (MS). Assessing everyday memory problems is crucial for monitoring the impact of memory deficits on individuals’ day-to-day lives and evaluating the effectiveness of interventions that aim to improve cognitive functions. The aim of this systematic review was to identify the research literature on everyday memory measures used with people with MS, describe the types of measures used, and summarise their psychometric properties. Empirical studies of cognitive function in MS using standardised everyday memory measures were included. Online databases (MEDLINE, PsycINFO, PsycARTICLES, Embase) and Google Scholar were searched. Forty-four studies met the inclusion criteria. A total of twelve measures were identified, with varied uses and administration methods. The majority of papers did not report any psychometric properties for MS populations. The few papers that did, reported that the measures have good reliability and appear to have good face, concurrent and ecological validity, but these need to be evaluated further. This review presents researchers and clinicians with an overview of the various everyday memory measures used in studies with people with MS, to help them choose the appropriate measure for their evaluations.